Evaluation of the implementation of the free Senior High School education program in North Sulawesi - Tuilan, Jeane; Mantiri, Jeane; Supit, Brain Fransisco; Rantung, Margareth I. R. (Academy of Education Journal, 2024)
The implementation of free education must be guaranteed to be implemented in accordance with existing government policies. One of them is evaluating the implementation of free education. This research aims to evaluate the implementation of the free senior high school education program in North Sulawesi Province. The research method used is a descriptive-qualitative method with purposive sampling technique. Data collection techniques include observation, interviews and documentation. The research results show that the evaluation was carried out to measure the extent to which free education was successfully implemented effectively and efficiently. Evaluation of the implementation of free education programs certainly does not necessarily always go according to what has been determined. By analyzing according to the evaluation approach implemented at State Senior High Schools in North Sulawesi, it can be concluded that the implementation of free education evaluation still does not meet the criteria for efficiency, equity, accuracy and responsiveness.